PENGARUH BUDAYA, SOSIAL, PRIBADI DAN PSIKOLOGIS TERHADAP KEPUTUSAN PEMBELIAN MIE INSTAN MEREK “MIE SEDAAP - Fathawati Fathawati; Muhammad Hufron; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACT Target of this research is to know influence cultural, social, psychological and personal by parsial to purchasing of noodles product of instan Noodles Mie Sedaap brand at student of university of Islamic Malang. To know influence cultural, social, psychological and personal by simultan to purchasing of noodles product of instan Noodles Mie Sedaap brand at student of university of Islamic Malang.Type this research is explanatory research. This research done at student Faculty Of Economics University of Islamic Malang school year 2013-2016 which consuming noodles of Sedaap amount to 1777 student while research sampel amount to 95 student with sampling technique of purposive sampling. Result of research indicate that variable cultural, social, personal, psychological have an effect by simultan to decision of purchasing of noodles instan Mie Sedaap brand. Variable cultural, social, personal, psychological by parsial have an effect to decision of purchasing of noodles instan Mie Sedaap brand.  Keyword : Cultural, Social, Personal, Psychological and Decision of Purchasing